The effect of internal corporate governance mechanisms on impression management in Malaysia - Al-Sayani, Yahya Mohammed Ahmed (2021)
Accounting narratives are an increasingly important medium of financial communication. Research suggests that such narratives are widely used and considered important in the investment decisions of private and institutional investors. However, there is a scarcity of research investigating the association between internal corporate governance mechanism and impression management (IM) as part of the presentation of corporate disclosure, especially voluntary disclosure. Nowadays, the issue of IM has become a concern, as accounting narratives are unaudited and thus may be subject to IM, especially in respect of corporate governance as an internal monitoring mechanism to ensure the financial reporting quality. This study examines the influence of board chairman characteristics (independence, tenure, ethnicity, age), board of directors’ characteristics (independence, gender, education, multiple directors), audit committee characteristics (independence, size, meeting, financial expert) and ownership structure (family, managerial, foreign) on IM based on agency and signalling theories. The sample consists of 268 firm-year observations on Bursa Malaysia for 2017 and 2018. This study reveals that chairman independence, tenure, and age, board education, and audit committee independence reduce IM practices and increase the quality of financial reporting. However, chairman ethnicity, board independence, multiple directorships, audit committee meetings, financial expertise, and family ownership increase IM practices and decrease the quality of financial reporting. The practices of managers to engage in IM can be controlled by corporate governance mechanisms especially, chairman independence, tenure and age, board education, and audit committee independence that show a negative relationship with IM. Meanwhile, chairman ethnicity, board independence, multiple directorships, audit committee meeting, financial expert and family ownership showed a positive relationship with IM practices. Based on the findings, this study contributes to a better understanding of IM practices and the internal corporate governance mechanism among Malaysian listed firms by providing a reference point for the relevant parties such as regulatory bodies, policymakers and standard setters towards improving the quality of the financial reporting and corporate governance practices in ensuring credible accounting information.